Anatomiczne i fizjologiczne podstawy unaczynienia nerwu wzrokowego - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
schemic disorders of the optic nerve constitute an important cause of visual loss. Therefore, to understand the pathogenesis of these diseases, it is imperative to be familiar with the vascular anatomy and physiology of the optic nerve. The purpose of this paper is to present a brief overview of the current state of knowledge on this topic. The blood supply of four anatomical regions of the optic nerve, factors influencing the optic nerve circulation and autoregulation mechanism are presented.